Mirounga leonina - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
4. Southern Elephant Seal Mirounga leonina French: Eléphant-de-mer austral / German: Siidlicher See-Elefant / Spanish: Elefante marino meridional Other common names: South Atlantic Elephant Seal, Southern Sea Elephant Taxonomy. Phoca leonina Linnaeus, 1758, “ad polum Antarcticum.” Restricted by O. Thomas in 1911 to “Juan Fernandez,” and further restricted byJ. E. Hamilton in 1940 to “Isla Mas a Tierra” (Chile). This species is monotypic. Distribution. Southern Ocean, breeding sites are scattered on subantarctic islands, Antarctic Peninsula, and the coast of S Argentina. Descriptive notes. Total length 450-500 cm (males) and ¢.300-350 cm (females); weight 1500-3000 kg (males) and c.600-800 kg (females). Newborns are ¢.125 cm in length and weigh c.45 kg. Southern Elephant Seals are the largest of the phocid carnivores and are greatly sexually dimorphic in size and shape; exceptionally large male Southern Elephant Seals may weigh ¢.3700 kg. Offspring are born with a black pelage that starts to molt near weaning when they are about three weeks old to a short silvery pelage that fades to brown dorsally and tan or yellow ventrally. Nose of male Southern Elephant Seals begins to elongate and chest and neck begin to broaden during puberty at ¢.5-6 years old. Upper and lower canine teeth of males are also much longer and more robust that those in females. Post-canine teeth in both sexes are very small and non-functional. Habitat. Except for breeding and molting, at sea in the Southern Ocean, sometimes near the Antarctic continent, particularly males. Adult Southern Elephant Seals occur briefly on land to breed (about one month for females and up to three months for males) and to molt (about one month), and young individuals sometimes haul-out at other seasons to briefly rest. Food and Feeding. Southern Elephant Seals primarily eat deep-water squid and fish. Prey consists of ¢.75% squid and ¢.25% fish. Cod icefish (Notothenia spp.) of the Southern Ocean are thought to be important prey when Southern Elephant Seals are ...